Implant Failure of Titanium Versus Cobalt-Chromium Growing Rods in Early-onset Scoliosis. Issue 6 (March 2016) - Shinohara, Kensuke; Takigawa, Tomoyuki; Tanaka, Masato; Sugimoto, Yoshihisa; Arataki, Shinya; Yamane, Kentaro; Watanabe, Noriyuki; Ozaki, Toshifumi; Sarai, Takaaki
Abstract : Study Design: Retrospective case series of one institute database. Objective: To investigate the differences in the metallic strength of rods used for implant failure in the dual growing rod technique and evaluate clinical outcomes. Summary of Background Data: The dual growing rod technique in which implanted rods extend with the growth of the spine is a useful treatment for early onset scoliosis. However, many complications, particularly those associated with rods, exist. Especially, the implant failure of growing rod focused on metallic strength is unknown. Methods: Thirteen patients (42 lengthening surgeries) who underwent surgery by this technique at our hospital from 2007 were divided into a titanium rod plus titanium connector group (T group, n = 4, 26 lengthening surgeries) and cobalt-chromium rod plus titanium connection group (C group, n = 9, 16 lengthening surgeries). The incidence of implant failure and the site of fracture were retrospectively investigated. Results: Implant failure occurred in three patients in the T group, because of rod fracture in two patients and connector fracture in one. In the C group, implant failure occurred in six patients, because of rod fracture in one patient and connector fracture in seven. Fracture occurred twice in two patients. The rod fracture rate decreased with the use of cobalt-chromium rods but the rate of connector fracture increased. We performed a stress distribution analysis using the finite element method to clarify the mechanisms underlying implant failure in both groups. Regardless of the rod type, the greater load was placed on the distal rod. However, differences in the metallic strength caused the rod to fracture when titanium rods were used and connectors (weak metallic strength) to fracture when cobalt-chromium rods were used. Conclusion: Rod fractures occurred more commonly with titanium rods and connector fractures with cobalt-chromium rods. Level of Evidence: 4